PENGARUH ANALISIS RASIO KEUANGAN EARLY WARNING SYSTEM (EWS) dan PRICE TO BOOK VALUE (PBV) TERHADAP HARGA SAHAM PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sisdyanti, Amalia; Adawiyah, Wiwiek Rabiyatul; Tohir, Tohir (Faculty of Economics and Business Universitas Jenderal Soedirman, 2016)
This research is associated research that was done at insurance companies, in which those companies are listed in Indonesia stock exchange (BEI) for the period of 2011-2014. This research entitled “the impact of finance ratio analysis Early Warning System (EWS) and Price to Book value (PBV) towards Indonesia stock exchange (BEI) Listed insurance companies’ stock prices”. The aim of this research is to analyse the impact of liquidity ratio, claim expenses ration, agents balance to surplus ratio, premium growth ratio, the adequacy of funds ratio, and price to book value towards Indonesia stock exchange (BEI) listed insurance companies’ stock prices of 2011-2014. This research used double regression model analysis as a tool of hypothesis test. The population is 12 companies which are taken from Indonesia stock exchange (BEI) listed insurance from 2011 until 2014. Meanwhile, the sample was taken using purposive sampling method, with the result of 9 companies. The result shows that: (1) the liquidity ratio has significance positive impact towards stock prices, (2) claim expenses ratio has no significance impact towards stock prices, (3) agents balance to surplus ratio has no significance impact towards stock prices, (4) premium growth ratio has no significance impact towards stock prices, (5) the adequacy of funds ratio has significance impact towards stock prices, (6) price to book value has significance impact towards stock prices.